Strategy of the Regional Disaster Management Agency in Tackling Disasters in Sukabumi City - Putri Amelia; Dine Meigawati; Rizki Hegia Sampurna (Program Pascasarjana Universitas Negeri Makassar, 2023)
Sukabumi City Regional Disaster Management Agency as an autonomous unit that was previously based on field level, which was followed up by Sukabumi Mayor Regulation No. 77 of 2020 concerning the Main Duties and Functions of BPBD located in Sukabumi City. Regional disasters that occurred in Sukabumi City were dominated by floods and landslides, in 2022 in January-March there were 54 hydrometeorologically controlled disasters. Types of disasters consist of floods, tornadoes, extreme weather, fires, and landslides. The results of the data are based on information derived from the Disaster Data Electronic Information System or called Si Edan. This research uses (Mintzberg et al., 2003) including goals/objectives, policies, and stages/programs. Qualitative research methods with a phenomenological approach, data collection techniques, namely observation, interviews and documentation. Data validation using triangulation techniques. Data analysis used includes 1). Data reduction; 2). Presentation of data; 3). Drawing conclusions. The Sukabumi City Regional Disaster Management Agency uses the concept of penta helix or multi-party where there are various elements that help in disaster management, The strategic policy of the Regional Disaster Management Agency is always seen from the index of areas that experience disaster-prone potential. Supporting factors in the stages of activities / programs are the many parties and volunteer communities that are ready to participate in disaster management activities.